Does Football Still Unite? A Critical Review of the Future of Indonesian Football - Gunawan Suswantoro; Zainudin Amali (Universitas Negeri Semarang, 2025)
Football is one of the most popular sports in Indonesia. Besides being popular, the money circulation in this sport is also very large. Because of the high interest of the people in football, football often becomes a unifying tool and even breaks down the barriers of difference in each event. However, football can also have a negative impact if it is managed poorly. Gambling cases that cause losses and violence in stadiums that often occur must be valuable lessons. This paper tries to make a review of the current condition of Indonesian football and its potential and threats. This paper will also provide strategic steps so that football can benefit the unity and integrity of the Indonesian nation.